The Provision of Licensed Financial Technology Lending From The Perspective of Cyber Law and Criminal Law in Indonesia - Karo Karo, Rizky; Prasetyo, Teguh (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This study undertakes an examination of the enforcement of legal provisions pertaining to licensed Financial Technology (FinTech) Lending, specifically from the vantage point of cyber law and criminal law. Furthermore, this article aims to provide an analytical framework and to educate users of FinTech lending regarding the legal liabilities that arise under both cyber law and criminal law within this domain. This research employed a normative juridical approach. The study exclusively utilized secondary data, comprising the 1945 Constitution, Law Number 1 of 2024 concerning the Second Amendment to Law Number 11 of 2008 regarding Information and Electronic Transactions (the ITE Law), and Law Number 4 of 2023 concerning the Development and Strengthening of the Financial Sector (IL 4/2023). This data underwent a qualitative analysis. FinTech lending providers bear criminal liability should they be found to have committed criminal acts under the Electronic Information and Transactions Law (UU ITE). It is therefore incumbent upon these providers to conduct their electronic operations in strict adherence to the principles of cyber law. Furthermore, the Financial Services Authority (OJK) is empowered to impose administrative sanctions upon FinTech lending providers proven to have misused personal data, in accordance with Indonesia Law Number 4 of 2023